Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Keputusan Pembelian Produk - Nuraini, Hilga; Hendratmoko, Christiawan (Journal of Trends Economics and Accounting Research, 2025)
This research was conducted in Solo Raya which covers 7 areas. This research aims to analyze the influence of product quality and price perception on purchasing decisions for Jims Honey product. Quantitative research methods were used. For the population in this study, the number of which was not found, using the formula shown by Hers, the sample used was 75 respondents using the purposive sampling technique. Data collection methods included questionnaires and literature reviews. Multiple linear regression analysis, t-tests, and coefficient of determination test were used for data analysis. The test results show that product quality and price perception significantly impact purchasing decisions for Jims Honey products. The existence of good and durable products at affordable prices makes consumers interested and will take action to repurchase products from the Jims Honey brand. Product quality and price perception explained 46% of the variation in purchasing decisions, while the remaining 54% was influenced by other variables outside the study.